A Sub-Acute Dosing Study of Saxitoxin and Tetrodotoxin Mixtures in Mice Suggests That the Current Paralytic Shellfish Toxin Regulatory Limit Is Fit for Purpose. - Finch SC; Webb NG; Boundy MJ; Harwood DT; Munday JS; Sprosen JM; Somchit C; Broadhurst RB (MDPI (Basel, Switzerland), 2023)
Paralytic shellfish poisoning is a worldwide problem induced by shellfish contaminated with paralytic shellfish toxins. To protect human health, a regulatory limit for these toxins in shellfish flesh has been adopted by many countries. In a recent study, mice were dosed with saxitoxin and tetrodotoxin mixtures daily for 28 days showing toxicity at low concentrations, which appeared to be at odds with other work. To further investigate this reported toxicity, we dosed groups of mice with saxitoxin and tetrodotoxin mixtures daily for 21 days. In contrast to the previous study, no effects on mouse bodyweight, food consumption, heart rate, blood pressure, grip strength, blood chemistry or hematology were observed. Furthermore, no histological findings were associated with dosing in this trial. The dose rates in this study were 2.6, 3.8 and 4.9 times greater, respectively, than the highest dose of the previous study. As rapid mortality in three out of five mice was observed in the previous study, the deaths are likely to be due to the methodology used rather than the shellfish toxins. To convert animal data to that used in a human risk assessment, a 100-fold safety factor is required. After applying this safety factor, the dose rates used in the current study were 3.5, 5.0 and 6.5 times greater, respectively, than the acute reference dose for each toxin type set by the European Union. Furthermore, it has previously been proposed that tetrodotoxin be included in the paralytic shellfish poisoning suite of toxins. If this were done, the highest dose rate used in this study would be 13 times the acute reference dose. This study suggests that the previous 28-day trial was flawed and that the current paralytic shellfish toxin regulatory limit is fit for purpose. An additional study, feeding mice a diet laced with the test compounds at higher concentrations than those of the current experiment, would be required to comment on whether the current paralytic shellfish toxin regulatory limit should be modified.
Keywords: dosing protocols; feeding study; paralytic shellfish toxins; saxitoxin; tetrodotoxin; toxicology; Humans; Animals; Mice; Saxitoxin; Tetrodotoxin; Shellfish Poisoning; Shellfish; Seafood